SIMULATION AND EXPERIMENTAL RESEARCH ON MILLING SURFACE TOPOGRAPHY BASED ON CUTTING VIBRATION - PAN LiMei; QIAN Wei; LIU Jin; YE Yi; GUO MiaoXian (Jixie qiangdu, 2022)
The surface topography of parts serves as a crucial role for machining quality. In order to achieve accurately prediction of the surface topography of precision milling, a surface topography simulation method based on wavelet packet analysis and frequency spectrum analysis of cutting vibration is proposed in this paper. In the paper, firstly, the ball-end milling is taken as the research object and the motion trace model of cutting edge changing with time based on the workpiece coordinate system is established. And then the vibration equation obtained by wavelet packet analysis and spectrum analysis is put into the model. Finally, the surface topography of the part is simulated and predicted by employing MATLAB. The comparisons between simulation and trial experiments suggest that the accuracy of the surface topography simulation prediction model based on wavelet packet analysis and frequency spectrum analysis of vibration signal offers a reference for the actual processing and production.